2010
DOI: 10.2478/v10001-010-0034-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of occupational exposure to arsenic on the nervous system: Clinical and neurophysiological studies

Abstract: Objectives: A number of metals, especially heavy metals, exhibit neurotoxic properties. Neurological and neurophysiological studies indicate that the functions of the central (CNS) and peripheral nervous system (PNS) may be impaired under conditions of exposure to arsenic (As). The aim of the present study was to assess the effects of inorganic arsenic on the central and peripheral nervous system. Materials and Methods: The study covered a group of 21 male workers (mean age: 41.9 yr; SD: 7.6; range: 31-55 yr) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 11 publications
0
33
1
1
Order By: Relevance
“…Some evidence in experimental models concerning neurotoxicity of other metals such as zinc and copper [88,89] is also present in scientific literature, but there is no strong evidence concerning relationship with ALS. Little evidence about occupational exposure to aluminum and the onset of neurological disorders compatible with degenerative motor neuron disease is present in scientific literature: Sińczuk-Walczak [90] has examined aluminium effects on the functions of the nervous system in people occupationally exposed to dust and fumes containing this metal. The author has mostly found neuro-behavioral and bioelectric cerebral disorders, and less frequently neurological symptoms correlated with a motor neuron disease.…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence in experimental models concerning neurotoxicity of other metals such as zinc and copper [88,89] is also present in scientific literature, but there is no strong evidence concerning relationship with ALS. Little evidence about occupational exposure to aluminum and the onset of neurological disorders compatible with degenerative motor neuron disease is present in scientific literature: Sińczuk-Walczak [90] has examined aluminium effects on the functions of the nervous system in people occupationally exposed to dust and fumes containing this metal. The author has mostly found neuro-behavioral and bioelectric cerebral disorders, and less frequently neurological symptoms correlated with a motor neuron disease.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognitive problems and subtle electroencephalographic changes have been observed in aluminum workers with urinary aluminum concentrations of the order of 41 μg/L, a level reached in one-third of our patients. 32,33 The prospect of fetal damage is even more worrying, because aluminum crosses the placenta and may become fixed in the fetal brain, disturbing its development. 12,34 Reports of psychomotor abnormalities in young rats born to dams fed clay during the gestation period seem to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of occupational exposure of workers in the copper smelter factory, the nature and localization of clinical and neurophysiological lesions, the characteristic feature of the optic neuron dysfunction and the correlations between biological monitoring parameters and inorganic arsenic levels in the workplace air strongly support the hypothesis of the predominating neurotoxic effect of inorganic arsenic. Compared to the studies reported earlier [22,23], results presented in this paper were obtained with the use of ICP-MS and apply to a different population of workers exposed to inorganic arsenic. Monitoring of the effects of occupational exposure to arsenic and its inorganic compounds on the nervous system, as well as the outcomes of determining urine concentrations of As species should contribute to the prevention of As exposure and provide the direction for further studies.…”
Section: Discussionmentioning
confidence: 92%